Children´s Participation Right in Health Care from the Perspective of Patient’s Human Rights (Revista Iberoamericana de Bioética, 2019)
This study consists of theoretical-normative research which aims to analyze children’s right to participate under art. 12 of the United Nations Convention on the Rights of the Child and its application in health care. It draws the conclusion that regardless the child’s capacity for informed consent, their participation is an ethical-legal requirement that must be applied to current Brazilian legislation and to the daily practice of health professionals.
Keywords: human rights; patient; child; participation